Pengaruh Kualitas Pelayanan Pre-Flight Gapura Angkasa Terhadap Kepuasan Penumpang Maskapai Citilink di Bandar Udara Internasional Yogyakarta - Bunga Indah Permata; Maria Valeria Roellyanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Transportation services are one of the basic human needs. In the current era of globalization, with increasing mobility of people or goods, the role of transportation modes becomes very important both in the economic and social fields. Service quality is also inseparable from the desire of service users to obtain good, comfortable, fast and safe transportation facilities and infrastructure. Service quality is a determining and important factor, so that service managers can determine the strategies that must be implemented in order to meet all the needs of service users safely, quickly and comfortably. This research aims to determine the influence of Gapura Angkasa pre-flight service quality on Citilink airline passenger satisfaction at Yogyakarta International Airport by distributing questionnaires to 100 Citilink airline passenger respondents. Based on research and data testing that has been carried out, it can be concluded that the influence of the quality of pre-flight service at Gapura Angkasa on Citilink airline passenger satisfaction is significant, namely based on the calculated T value of Variable X (Service Quality) on Variable Y (Passenger Satisfaction) of 11,083 more than T table 1,985. So it can be concluded that the quality of Gapura Angkasa's pre-flight service has a significant effect on Citilink airline passenger satisfaction. The magnitude of the influence of the quality of pre-flight service at Gapura Angkasa on passenger satisfaction is proven by the coefficient of determination value of 55.6%, which means that Variable X (service quality) has an influence of 55.6% on Variable Y (passenger satisfaction).